Geothermal Well Casing Design with High Temperature and Corrosive in Q Field - Raka Wardana; Muhammad Akhwan (Universitas Islam Riau (UIR) Press, 2023)
Casing design is the most crucial phase of drill a geothermal well. As most of problems could be prevented beforehand by having an excellent well casing design. Prior and present well problems may be assessed to enhance casing design mitigate leading causes and its relationship to well casing. This research is about geothermal well casing design by analyzing in advance the problems that the casing may encounter during drilling and production through NPT & casing damage analysis. The purpose is to construct design depth and grade of geothermal well casing from the effects of axial, hoop, and thermal stress, as well as corrosion. The method used is to analyze the NPT from the available DDR data of the wells and then analyze the damage that occurs to the production wells which then the results of these analysis’ become recommendations for of the next well casing design. The results show Well FDL-33 will use tie-back system with surface casing 20” K55 133 ppf at 350 mMD with semi-premium connection, production casing 13-3/8” L80 68 ppf at 1475.8 mMD with premium connection, production tieback casing 13-3 /8” L80 68 ppf at 300 mMD with premium connection, and production liner 9-5/8” L80 40 ppf at 2695.3 mMD with semi-premium connection.